Survey on Eu 27 Budgets: Main Revenues - Adrian Mihai INCEU; Dan Tudor LAZĂR; Paul ZAI; Mihai BABICI (Transylvanian Review of Administrative Sciences, 2009)
In this study we present an analysis of themajor aspects concerning the budgets of the EUcountries. The analysis took into considerationthe main revenues of the budgets of these 27 EUcountries. Our analysis concerns itself with thetotal income, taxes (total), social contributions(total) and other incomes. Analysis of main trendsof the budgets of the European Union countrieswill be achieved by calculating several indicators,namely: fixed-based indices, chain-based indices,minimum, maximum, average, percentages andpercentages of total GDP.